PENENTUAN KONDISI OPTIMUM HPLC UNTUK PEMISAHAN RESIDU PESTISIDA IMIDAKLOPRID, PROFENOFOS DAN DELTAMETRIN PADA CABAI (Capsicumannum ) - Nurhamidah Nurhamidah (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2005)
The research aim was to determine the optimum ratio and flow rate of mobile phase of acetonitrile: water for separation of pesticide residue of imidacloprid, profenofos and deltamethrin simultaneously with HPLC. The compromise wavelength of the three of residues was measured with UV–VIS spectrophotometer. The ratio of acetonitrile:water consisted of 70 : 30, 60 : 40, 50 : 50, 40 : 60 and 30 : 70 v/v, and the flow rate of the mobile phase consisted of 0,5, 0,75 and 1 mL minutes-1, respectively. The results show the optimum mobile phase was achieved at a ratio of 60:40 v/v and at a wavelength of 270 nm with retention tim of imidacloprid, profenofos and deltamethrin components achieved at 3.0, 6.2 and 17.1 minutes, respectively. The higher ratio of acetonitrile: water and higher mobile phase resulted in accelerating its retention time and a good separation of imidacloprid was not achieved. An unstatisfied separation was also obtained when smaller ratio of acetonitrile: water and lower mobile phase was used. It occurred due to higher deltametrin retention time.